THE TRANSFORMATIVE POTENTIAL OF YOGA IN ORGANIZATIONS - Thate, Rupesh Vitthal; Bachhav, Shreekala P. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Yoga's transformative potential is increasingly recognized in corporate settings, offering a holistic approach to enhancing individual and organizational well-being. This paper explores the multifaceted benefits of integrating yoga into the workplace, examining its impact on both employees and the overall organizational environment. For individuals, yoga provides effective stress management techniques, leading to reduced anxiety, burnout, and improved overall psychological health. Furthermore, regular yoga practice enhances focus, concentration, and cognitive function, contributing to increased productivity and improved decision-making. Beyond the cognitive benefits, yoga cultivates emotional intelligence, self-regulation, and self-compassion, fostering a more positive and resilient workforce. The physical benefits of increased flexibility, strength, and balance contribute to overall well-being and reduced health-related costs. At the organizational level, yoga fosters a more positive and supportive work environment, leading to increased employee engagement and job satisfaction. By promoting a sense of community and connection, yoga enhances teamwork and collaboration, while also fostering creativity and innovation through a more open and receptive mindset. Moreover, yoga's emphasis on mindfulness and ethical conduct can positively influence organizational values and promote sustainable business practices. This paper also addresses the practical considerations of implementing yoga programs in the workplace, including various formats, creating a supportive environment, and measuring program effectiveness. Ultimately, this exploration highlights the transformative potential of yoga to create a healthier, more productive, and ethically conscious corporate culture.